Improvement of the regulatory legal basis of meat processing enterprises as a factor of product quality management - Strashynska, Larysa; Sheremet, Oleg (My University, 2021)
The article emphasizes the need for systemic changes in the meat processing industry of Ukraine in the direction of improving the regulatory framework. The priority directions of improving the legislative support of the agricultural sector of the economy as a whole and the meat product subcomplex are outlined. The need to form a comprehensive system of measures for state regulation of the meat market in Ukraine, which would be based on the implementation of international standards, which are adapted to those developed by the Commission of the Code of Alimentarius. The system of meat product quality management is considered, which should be based on international standards ISO 9000, HACCP industry standards and others, which allow to increase the level of safety of production processes and the quality of finished products for both producers and consumers. A number of competitive advantages obtained by meat processing enterprises that implement a product quality management system in accordance with the requirements of ISO 9000 standards are substantiated. It is noted that maximizing the positive result for the company with the fullest use of opportunities provided by the implementation of quality management system in accordance with ISO 9000, is not possible without taking into account and minimizing the impact of threats that also accompany this process. The stages of implementation of the product quality management system at the enterprises in accordance with the requirements of ISO 9000 and the algorithm of realization of this process are determined. It is noted that the introduction and effective operation of the meat quality management system in accordance with the requirements of ISO 9000 should be implemented comprehensively, taking into account all the opportunities and threats that arise, and following a clear algorithm that includes time intervals for completion, re audits, involvement of external experts and intensification of internal services. У статті наголошено на необхідності системних перетворень в м’ясопереробній галузі України в напрямі вдосконалення нормативно-правової бази. Окреслено пріоритетні напрями удосконалення законодавчого забезпечення аграрного сектору економіки в цілому та м'ясопродуктового підкомплексу. Актуалізована необхідність формування цілісної системи заходів державного регулювання ринку м'яса в Україні, яка б базувалася на впровадженні міжнародних стандартів, які адаптовані до тих, що розроблені Комісією Кодексу Алементаріусу. Розглянуто систему управління якістю м'ясопродукції, яка повинна спиратися на міжнародні стандарти ІSО 9000, галузеві стандарти НАССР та інші, які дозволяють підвищувати рівень безпечності виробничих процесів та якість готових продуктів як для виробника, так і для споживача. Обґрунтовано низку конкурентних переваг, які отримують підприємства м’ясопереробної галузі, що впроваджують систему управління якістю продукції відповідно до вимог стандартів ІSО 9000. Зазначено, що максимізація позитивного результату для підприємства при найбільш повному використанні можливостей, що надає впровадження системи управління якістю відповідно вимог стандарту ISO 9000, не можлива без урахування та мінімізації впливу загроз, які також супроводжують даний процес, та окреслено ці загрози. Визначено етапи впровадження системи управління якістю продукції на підприємствах відповідно до вимог ІSО 9000 та алгоритм реалізації даного процесу. Зазначено, що введення та ефективне функціонування системи управління якістю м’ясопродукції відповідно до вимог стандартів ISO 9000 має реалізовуватись комплексно з урахуванням усіх можливостей та загроз, що виникають при цьому, та з дотриманням чіткого алгоритму, який заздалегідь включає часові проміжки на доопрацювання, проведення повторних аудитів, залучення сторонніх експертів та активізацію діяльності внутрішніх служб.
Keywords: кафедра економіки праці та менеджменту; кафедра маркетингу; regulatory framework; product quality; state policy; product competitiveness; ISO 9000 standards; meat processing enterprises; нормативно-правова база; якість продукції; державна політика; конкурентоспроможність продукції; стандарти ІSО 9000; м’ясопереробні підприємства